Analisis Employability Skill dan Literasi Sains Siswa Melalui Authentic Self-Assessment pada Kurikulum Merdeka di SMA Aceh Utara - Agus Muliaman; Halimatus Sakdiah; Fajrul Wahdi Ginting (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
Employability Skills and scientific literacy are abilities that students must have to become superior human resources and the ability to take on the challenges of 21st-century developments. The measurement of these skills is carried out by utilizing an assessment instrument in the form of Authentic Self-Assessment. This type of research is descriptive qualitative, the study population is students in North Aceh and the sample is taken randomly to analyze these two skills. Data analysis uses the stages of data collection, data reduction, data presentation, and data verification. The results obtained are the workability and scientific attitude of students are in the very good category, this shows that the implementation of the independent curriculum in schools is also very good.